2020
DOI: 10.3390/cryst10070565
|View full text |Cite
|
Sign up to set email alerts
|

Performance Comparison of Eichhornia crassipes and Salvinia natans on Azo-Dye (Eriochrome Black T) Phytoremediation

Abstract: Organic pollutants, such as dyes, have a negative effect on the aqueous environment, therefore, their elimination from water bodies is a high priority. In this work, Eichhornia crassipes and Salvinia natans, both model plants with high phytoremediation efficiency, were exposed to various concentrations (Ci = 50–500 mg/L) of Eriochrome Black T (EBT). Their capacity to assimilate EBT was studied for 16 days of exposure, similar to natural conditions and by spectrophotometric monitoring of the dye concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 44 publications
0
5
0
1
Order By: Relevance
“…After that, the samples were examined by Scanning Jeol JEM 5510 JV SEM, and studied with Oxford Instruments EDS Analysis System Inca 300 (UK) to examine its elemental composition. EDX measurements help to identify the elemental composition (Rápó et al 2020).…”
Section: Methodsmentioning
confidence: 99%
“…After that, the samples were examined by Scanning Jeol JEM 5510 JV SEM, and studied with Oxford Instruments EDS Analysis System Inca 300 (UK) to examine its elemental composition. EDX measurements help to identify the elemental composition (Rápó et al 2020).…”
Section: Methodsmentioning
confidence: 99%
“…As the dye concentration increased, there was a corresponding decrease in the amount of chlorophyll present in the plants. [29] Another significant source of dye contamination in water bodies is Toluidine Blue, a phenothiazine dye which has been reported to have mutagenic effects and is hazardous to both DNA and RNA. These findings highlight the importance of responsible dye usage, proper disposal, and effective wastewater treatment processes to minimize the environmental and health risks associated with dye pollutants.…”
Section: Impact Of Textile Dyes On Aquatic Environmentsmentioning
confidence: 99%
“…Studies indicated that the stress imposed by the dye led to alterations in the photosynthetic pigments, as evidenced by changes in the carotenoid‐to‐chlorophyll ratio. As the dye concentration increased, there was a corresponding decrease in the amount of chlorophyll present in the plants [29] . Another significant source of dye contamination in water bodies is Toluidine Blue, a phenothiazine dye which has been reported to have mutagenic effects and is hazardous to both DNA and RNA.…”
Section: Adverse Effect Of Textile Dyesmentioning
confidence: 99%
“…Salvinia natans (L.) All. ( S. natans ) is a free-floating fern from the Salviniaceae family and has a high tolerance to a wide range of pollutants and a rapid growth rate [ 22 ]. It is native to Europe and widely spread within temperate, tropical, and subtropical regions [ 16 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%